Impact of old and very old age on outcomes in patients with acute ischemic stroke undergoing endovascular therapy. (25th November 2020) - Proietti, M; Mascolo, A.P; Maramma, F; Morosetti, D; Da Ros, V; Gandini, R; Alemseged, F; Diomedi, M; Koch, G; Sallustio, F
Abstract: Background and purpose: Only a restricted number of elderly patients has been included in the majority of recent endovascular stroke trials. We provided an analysis about differences in outcomes after mechanical thrombectomy (MT) according to age. Methods: A retrospective analysis of an observational registry of patients with anterior large vessel acute ischemic stroke was performed. Main analysis was performed comparing patients <80 vs. ≥80 years old. A sensitivity analysis was performed comparing 3 age groups: i) <80 years; ii) 80–84 years; iii) ≥85 years. Outcomes were: i) any hemorrhagic infarction; ii) alive with disability; iii) death; iv) a composite outcome of alive with disability/death. Results: 615 patients were identified. 227 (36.9%) patients were ≥80 years old, with 115 (18.5%) ≥85 years old. Elderly (≥80 years) patients showed a higher modified Rankin Scale (mRS) at discharge and 3-months follow-up (F=9.819, p=0.001) [Figure 1]. Comparing the three groups (<80 years, 80–84 years, ≥85 years) a progressively higher mRS was found at discharge and 3 months follow-up (F=4.899, p=0.008). A progressively higher rate of death and composite outcome between the age groups was found, both in the main and sensitivity analyses. In the logistic regression analysis age ≥80 years was found associated with an increased risk of death (odds ratio [OR]: 2.25, 95% confidence interval [CI]: 1.27–4.00) and showed a trend in higher risk for composite outcome (OR: 1.61, 95% CI: 0.92–2.281). No difference was found between 80–84 years and <80 years patients, while very elderly (≥85 years) had an increased risk of death (OR: 2.85, 95% CI: 1.60–5.10) and composite outcome (OR: 2.37, 95% CI: 1.30–4.33). Conclusions: In our analysis elderly patients have an increased risk of death and composite outcome of disability and death. In particular, this risk appears to be significantly higher in very elderly patients (≥85 years old). Funding Acknowledgement: Type of funding source: None